Improving educational research for national development (2012)
This paper examined the concept of research and the relevance of research undertakings to research practitioners and the society at large. Consequently, the paper explored those areas where challenges of research could be found and suggests strategies on how to resolve the problems among which are that federal and state governments and operational arm of non-governmental organizations should help fund research in Nigeria and that a healthy relationship should be established between the supervisors and supervisee in other to ensure that mentor actually tranfered essential and useful rudiment of research for sustainable development to the mentee who would carry on the duty of effective research after they have stepped aside. Finally, the paper also highlighted some viable area of focus for researchers and research practitioners that are most likely to benefit and assisted in carrying out research for sustainable national development in Nigeria